Water quality and sediment characteristics of Sampadi River - Mildred, Eklip (Universiti Malaysia Sarawak (UNIMAS), 2010)
This study waS to find out about the status of Sampadi River by doing water quality assessment (chemical characteristics) and sediment study, Current information on the impact of different land uses such as aquaculture and urban areas on the water and sediment quality ofSampadi River have not yet been reported. Four trips to the sampling stations were done. and the results show some high values of Total Kjeldahl Nitrogen (TK."!) and Total Phosphorus (TP) at river near the oil palm plantation and aquaculture shrimp farm, The five·day biological oxygen demand (BOD,) at all of the stations violated Class III of INWQS Malaysia. Chemical oxygen demand at all stations of the river violated class lIB, The station near jetty areas shows the highest concentration for Lead (0.1012 mg/L). Nickel (0.2741 mg/L), Zinc (0.2696 mg/L) and Cadmium (0.1040 mgIL). meanwhile. the station near village shows the highest concentration lilr Copper (0.6176 mglL) and Chromium (0.3426 mg/L). For heavy metals in sediment. based on Ontario Sediment Quality Guidelines, cadmium (0.70 mg/L) found at sediment near the jetty and chromium (29,8 mgfL) at the station near oil palm plantation, indicates the lowest effect level. For nickel. all of the stations studied exceed the lowest effect level concentration. For TKN, only the station near oil palm plantation exceeded the lowest effect level concentration. P04 3 --P concentration in sediment at all stations of the S.mp.di River are in the no effect level.